The effect of squat depths on peak forces during countermovement jumps - Etiennette, D.; Williams, H.; Rich, C.; Cole, Z. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The vertical jump is a key fundamental skill which is applied across a range of sports (Swinton, et al., 2010). The aim of the study was to examine the influence of squat depths on peak force, maximal jump height and maximal power on countermovement jump performance. We hypothesized that an increase in squat depth would generate an increase in jump height and power due to the greater time for force generation at take-off. The purpose of this study was to establish a guideline for coaches and athletes to be used in training programs, to determine the optimal squat depth for the athlete.